A new pretest probability score for diagnosis of lower limb deep vein thrombosis in unselected population of outpatients and inpatients. (March 2017) - Sermsathanasawadi, Nuttawut; Chaivanit, Trakarn; Suparatchatpun, Pinyo; Chinsakchai, Khamin; Wongwanit, Chumpol; Ruangsetakit, Chanean; Mutirangura, Pramook
Objective: To develop a new pretest probability score for deep vein thrombosis (DVT) in unselected population of outpatients and inpatients. Methods: The new score was developed using independent factors from 500 patients clinically suspected of leg DVT. The new score was validated in a second group of 315 patients. Results: The score consists of four components: unilateral leg pain, confinement to bed, calf enlargement >3 cm compared with the other side, and previous venous thromboembolism. A score ≥2 indicated a high probability while a score <2 indicated low probability. The sensitivity and specificity of the new score were 71.60% and 79.49%, respectively. The area under the receiver operating characteristic curve for the new score was 0.79. The combination of a new score <2 and D-dimer level <500 µg/L had a negative predictive value of 96.43%. Conclusions: Our new score was valid in an unselected population of outpatients and inpatients.